Inter-religious dialogue activity: an experience among undergraduate students in selected universities in Malaysia - Khadijah Mohd Khambali @ Hambali; Nur Farhana Abdul Rahman; Azarudin Awang; Alwani Ghazali; Mohsem Sallam, Abdul Nasser Sultan (Penerbit Universiti Kebangsaan Malaysia, 2019)
The study is aimed at exploring a few inter-religious dialogue activities among undergraduate students in the Department of Aqidah and Islamic Thought, the Academy of Islamic Studies, University of Malaya (JAPI, UM); the Academy of Contemporary Islamic Studies, (UiTM);the Department of Usuluddin and Philosophy, National University of Malaysia (JUF, UKM) and the Center for the Promotion of Knowledge and Language, University Malaysia of Sabah (UMS).There are many courses related to religious studies that are taught at these four universities. The lived-experiences of the participants were explored through inter-religious dialogue activities. A purposive sample of various students from the four universities mentioned above participated in this dialogue activity. The data were analyzed using an interpretive phenomenological approach, inductively in order to characterize the received data into respective themes. Hence, the results demonstrated that the lived-experience of the dialogue activities in inter-religious dialogue was characterized by the following: (1) the role of the environment, (2) the value of individual relationships through sharing and storytelling and (3) the experience and relationships among other ethnicities as well as family child-rearing practices. Thus, this study provides information concerning the various dialogue activities of inter-religious dialogue models and designs in universities in Malaysia and proposes that different models and designs of interreligious dialogue rely on different types and goals. This study also recommends the significance of creating environments to foster inter-religious dialogue, expanding the formats of interfaith dialogue and increasing religious study through education and training.